2012
DOI: 10.1590/s0100-55022012000200026
|View full text |Cite
|
Sign up to set email alerts
|

O PET-Saúde no Centro de Saúde Cafezal: promovendo hábitos saudáveis de vida

Abstract: RESUMO Trata-se de um de relato de experiência dos monitores bolsistas e voluntários de alguns cursos da área de saúde da Universidade Federal de Minas Gerais (UFMG) no projeto PET- ABSTRACT This is an experience report of the scholarship students and volunteers of health science courses of the Federal University of Minas Gerais (UFMG) who participated in the PET

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
1
3
0
2
Order By: Relevance
“…This significant learning occurs in this context from the time the PET-Saúde provides the contact of the students with the services and the territory of a community. This result corroborates the findings of other authors who have studied the participation of students in PET-Saúde 4,[6][7][8][9][20][21][22][23] . It is noteworthy that, in this perspective, it is important to be assigned a meaning to this approach of future health professionals with the people, not being relevant only to enter on the practice field in a single and isolated manner.…”
Section: Recognition Of the Health Needssupporting
confidence: 92%
See 1 more Smart Citation
“…This significant learning occurs in this context from the time the PET-Saúde provides the contact of the students with the services and the territory of a community. This result corroborates the findings of other authors who have studied the participation of students in PET-Saúde 4,[6][7][8][9][20][21][22][23] . It is noteworthy that, in this perspective, it is important to be assigned a meaning to this approach of future health professionals with the people, not being relevant only to enter on the practice field in a single and isolated manner.…”
Section: Recognition Of the Health Needssupporting
confidence: 92%
“…In this context, PET-Saúde contributes by shooting in the Subject the critical thinking about their training process, and the relevance of learning and reflections experiences 13,14,[20][21][22][23] . The dialogic and interdisciplinary spaces present in the PET-Saúde allow the student to view the existing limit on your current training, predominantly reduced to propositions and practical techniques.…”
Section: Experience Of New Learning Practicesmentioning
confidence: 99%
“…Several studies have reported the impact of PET-Health on education, however, most consider experiments involving one 11,20,21,22,23,24 or two institutions of higher education 25,26 , in most cases only reporting situations present in specific groups 27,28 . The purpose of this study was to extrapolate these specific situations, seeking an analysis of all the undergraduates of Dentistry, Medicine and Nursing who participated in the 2010 ENADE, which would allow for comparing the performance of those linked to the PET-Health with non-PET students, whereas the program should display the same references in all participating higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Os autores Prado e Carvalho (2012), Alonso e Carvalho (2012), Campos et al (2012), Dias et al (2012), Ferreira et al (2012) e Teixeira et al (2012) enfatizam que a experiência de inserção discente no PET-Saúde propicia um ambiente de aprendizado ímpar ao aproximar estudantes de profissionais e usuários do SUS na esfera da comunidade. Isso contribui para que as atividades sejam diversificadas e com amplas possibilidades de questões a serem discutidas tendo em vista o grupo multiprofissional, a experiência de vida e profissional de cada integrante e, também, as peculiaridades locais de cada serviço de saúde.…”
Section: A Integração Ensino-serviço a Partir Do Pet-saúde Como Um Pounclassified